Portmahomack : monastery of the Picts - Carver, M. O. H. (EUP, 2016)
Portmahomack today is a serene fishing village on the Dornoch Firth, north east Scotland where archaeological excavations have written a new history of the origins of Scotland. This book brings alive the expedition and its discoveries, most famously a monastery of the eighth century in the land of the Picts. Starting from chance finds of a Pictish carved stone in St Colman's churchyard, the archaeologists unearthed four settlements one on top of the other. An elite farm was succeeded by the Pictish monastery, which, following a Viking raid in AD800, became a trading place and then a medieval vi.